2019
DOI: 10.1101/2019.12.18.880799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitin Links Smoothened to Intraflagellar Transport to Regulate Hedgehog Signaling

Abstract: In the absence of hedgehog ligand, patched-1 (Ptch1) localizes to cilia and prevents ciliary accumulation and activation of smoothened (Smo). Upon ligand binding, Ptch1 is removed from cilia, Smo is derepressed and accumulates in cilia where it activates signaling. The mechanisms regulating these dynamic movements are not well understood but defects in intraflagellar transport components including Ift27 and the BBSome cause Smo to accumulate in cilia without pathway activation. We find that in the absence of l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…GRK2 was shown to phosphorylate SMO C‐tail, leading to ciliary accumulation of SMO and Hh pathway activity (Chen et al , 2011); the former has been disputed and appears cell context dependent (Zhao et al , 2016; Pusapati et al , 2018). GRK2‐mediated SMO phosphorylation was shown to induce β‐arrestin (ARRB) recruitment, leading to KIF3A‐dependent cilia accumulation of SMO (Chen et al , 2004; Kovacs et al , 2008); however, later studies showed normal cilia accumulation of SMO in ARRB knock‐out cells (Pal et al , 2016; Desai et al , 2020). Ligand‐dependent removal of the Hh pathway inhibitor GPR161 was shown to depend on GRK2 activity (Pal et al , 2016; Pusapati et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…GRK2 was shown to phosphorylate SMO C‐tail, leading to ciliary accumulation of SMO and Hh pathway activity (Chen et al , 2011); the former has been disputed and appears cell context dependent (Zhao et al , 2016; Pusapati et al , 2018). GRK2‐mediated SMO phosphorylation was shown to induce β‐arrestin (ARRB) recruitment, leading to KIF3A‐dependent cilia accumulation of SMO (Chen et al , 2004; Kovacs et al , 2008); however, later studies showed normal cilia accumulation of SMO in ARRB knock‐out cells (Pal et al , 2016; Desai et al , 2020). Ligand‐dependent removal of the Hh pathway inhibitor GPR161 was shown to depend on GRK2 activity (Pal et al , 2016; Pusapati et al , 2018).…”
Section: Introductionmentioning
confidence: 99%